2010
DOI: 10.1158/1078-0432.ccr-10-0286
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hypoxic Cells through the DNA Damage Response

Abstract: Exposure to hypoxia-induced replication arrest initiates a DNA damage response that includes both ATR-and ATM-mediated signaling. DNA fiber analysis was used to show that these conditions lead to a replication arrest during both the initiation and elongation phases, and that this correlated with decreased levels of nucleotides. The DNA damage response induced by hypoxia is distinct from the classical pathways induced by damaging agents, primarily due to the lack of detectable DNA damage, but also due to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…For instance, we have previously demonstrated that inhibition or loss of the Chk1 or ATR increased sensitivity to hypoxia/ reoxygenation [11][12][13][14]. We propose therefore that, additional studies focused on components of the hypoxia-induced DDR have the potential to establish new therapeutic targets [13].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, we have previously demonstrated that inhibition or loss of the Chk1 or ATR increased sensitivity to hypoxia/ reoxygenation [11][12][13][14]. We propose therefore that, additional studies focused on components of the hypoxia-induced DDR have the potential to establish new therapeutic targets [13].…”
Section: Introductionmentioning
confidence: 93%
“…We propose therefore that, additional studies focused on components of the hypoxia-induced DDR have the potential to establish new therapeutic targets [13].…”
Section: Introductionmentioning
confidence: 99%
“…ATM and ATR are activated, but without focus formation, consistent with the absence of strand breaks. Studies have demonstrated that hypoxia causes S-phase arrest and hinders the ability to restart replication in S-phase cells after prolonged hypoxia (2,3). Hypoxia also leads to substantially reduced dNTP pools via ribonucleotide reductase inhibition, accounting for the stalled replication (2,3).…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…Studies have demonstrated that hypoxia causes S-phase arrest and hinders the ability to restart replication in S-phase cells after prolonged hypoxia (2,3). Hypoxia also leads to substantially reduced dNTP pools via ribonucleotide reductase inhibition, accounting for the stalled replication (2,3). DNA repair pathways that are downregulated in hypoxia include DNA mismatch repair (MMR) and homology-directed repair (HDR) via specific transcriptional and post-transcriptional mechanisms (4,5).…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…In addition, tumor hypoxia is a driving force of genetic instability and is pivotal in cancer development and chemoresistance (1,(21)(22)(23). Hypoxic cancer cells usually exhibit dysregulated DNA repair (24)(25)(26), but data conflict about the functional status of the NHEJ repair pathway under hypoxia (27)(28)(29). The molecular basis of DNA repair-mediated chemoresistance under hypoxia thus deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%